Distribution Of Joint Properties According To Balanced Justice Principle - M Ridwan; Gugun Gumilar; Amran Suadi; KN Sofyan Hasan; M Syaifuddin (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
The structure of joint property divided governed by Law No. 1 of 1974, and the Compilation of Islamic Law must fully reflect the importance of justice and legal clarity. Based on that, the issue addressed in this journal is how to design a more reasonable and legally specific partition of the joint property after divorce for the community in the relevant marital law in the future. This study is categorized as legal-normative research. According to the study's findings, the future concept of joint property law reconstruction is to incorporate the principle of balanced justice based on Pancasila into Article 37 of Law Number 1 of 1974 concerning Marriage and Article 97 of the Compilation of Islamic Law through amendments to Article 37 of Law Number 1 of 1974 and Article 97 of the Compilation of Islamic Law. The notion of balanced justice has been found in various Republic of Indonesia's Supreme Court decisions. As a result, some of the legal rules in the joint property decision must be reviewed while developing joint property law regulations.